Speech Representation of Female Images in the Polycode Text of “Heroic” Cycle Cartoons of the Art Studio “Melnitsa” - E. N. Ilyina (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the study of the verbal component of animated films with a folk precedent basis. The relevance of the research is due to the need to study the conceptosphere of modern media texts conveying folklore imagery. The results of a comparative analysis of female images in animated films about Russian heroes are presented (Alyosha Popovich and Tugarin Zmey (2004), Dobrynya Nikitich and Zmey Gorynych (2006), Ilya Muromets and Nightingale the Robber (2007) in comparison with their folk prototypes. The issues of speech representation of the images of the mother and the bride / wife of a hero, traditional for the epic genre, as well as other female images, the appearance of which is due to the influence of other precedent sources, are considered. The conceptual proximity of the narrative-story line basis and the composition of the characters of the texts under study to the Russian fairy tale is proved. Particular attention is paid to the implementation of the stylistic technique of burlesque travesty, it is proved that this technique is the main means of creating a comic effect and performs a text-forming function in the studied polycode content. The scientific novelty of the work is seen in the fact that the verbal component of the animated films studied was not previously the subject of linguistic analysis.